A practical guide for researchers and reviewers using the ABCD Study and other large longitudinal datasets. (June 2022) - Saragosa-Harris, Natalie M.; Chaku, Natasha; MacSweeney, Niamh; Guazzelli Williamson, Victoria; Scheuplein, Maximilian; Feola, Brandee; Cardenas-Iniguez, Carlos; Demir-Lira, Ece; McNeilly, Elizabeth A.; Huffman, Landry Goodgame; Whitmore, Lucy; Michalska, Kalina J.; et al.
Abstract: As the largest longitudinal study of adolescent brain development and behavior to date, the Adolescent Brain Cognitive Development (ABCD) Study® has provided immense opportunities for researchers across disciplines since its first data release in 2018. The size and scope of the study also present a number of hurdles, which range from becoming familiar with the study design and data structure to employing rigorous and reproducible analyses. The current paper is intended as a guide for researchers and reviewers working with ABCD data, highlighting the features of the data (and the strengths and limitations therein) as well as relevant analytical and methodological considerations. Additionally, we explore justice, equity, diversity, and inclusion efforts as they pertain to the ABCD Study and other large-scale datasets. In doing so, we hope to increase both accessibility of the ABCD Study and transparency within the field of developmental cognitive neuroscience.